PENGARUH METODE NATURE LEARNING TERHADAP KEMAMPUAN MENULIS PUISI DENGAN BERBANTUAN MEDIA AUDIO VISUAL KELAS VIII SMP NEGERI 05 PERCUT SEI TUAN - Elsalina Mei Angel Br Girsang; Muharrina Harahap (STKIP Subang, 2026)
This study aims to determine the effect of the Nature Learning method assisted by audiovisual media on the poetry writing skills of eighth-grade junior high school students in the 2024/2025 academic year. This study used a quantitative method with a Two-Group Posttest Only Design. The study sample consisted of 66 students, consisting of classes VIII-7 as the experimental class and classes VIII-8 as the control class. Data were obtained through a poetry writing test and analyzed using normality tests, homogeneity tests, and t-tests.The results showed that the poetry writing skills of students taught using the Nature Learning method assisted by audiovisual media were better than those taught using conventional methods, with the average score of the experimental class (82) being higher than that of the control class (74). Through hypothesis testing, the calculated t-test was 4.81 and the table t-test was 2.00 at α=0.05, thus accepting H_a (4.81>2.00